THE REFERENTS OF CENDANA IN MEDIA DISCOURSE A: Study of Metonymic Use of Place Name - Muhammad Adam (Prosiding Seminar Nasional Bahasa, Sastra, dan Seni (Sesanti), 2019)
Since the resignation of Indonesian second president-Soeharto twenty one years ago, his private residence’s address is still used by media till today to refer to him, to his family, to political party affiliates to him and everything associates to him. This research looks into the metonymic use of cendana, the street address of the second Indonesian president - Soeharto’s residence, Cendana Street No.8-Menteng, Central Jakarta. The aims of the research are to study the metonymic use of cendana in Indonesian media discourse to analyze the collocation of cendana in metonymic use, and to identify the exact referents. The method is descriptive qualitative, the source of data are from thirty news article from two mainstream Indonesian online media, Detik and Tempo. The results show that there are in total five collocations of cendana in metonymic use exclude the use of only the word cendana and the referents of the metonymic use is extended not only to Soeharto’s off springs but also to his brother, and other relatives. The contexts of discourse mostly used in political discourse,andsomeothersareinlaw,economyandentertainment discourse. The metonymic use of cendana by Indonesian media implies that the family still holds a big influence in Indonesian political landscape. The result also shows that Tommy Soeharto is the most dominant referent for the metonymic use of cendana and its collocation, whereas keluarga cendana (cendana family) is the most dominant collocation.